The Use Of Question And Answer Method To Improve Student Achievement - Suprihatmojo, Agus (Social, Humanities, and Educational Studies (SHES): Conference Series, 2022)
The use of question and answer method to improve student achievement. The study aimed to improve student achievement for all subjects. This research design is in the form of stages which are recycling processes starting from the planning, implementation, observation, and conclusion stages. From the stages of activity obtained the following results: Initial conditions, the percentage of children who excel is 40%. This is due to: (a) Many students are silent and passive; b) The teacher's voice is less clear. In the final condition, with the question and answer method, students who obtained scores above KKM increased to 80% as expected. This is due to the interaction between teachers and students, in the delivery of material the teacher's voice is clearly heard. From the results of the analysis, it can be concluded "Through the use of the question and answer method, it can increase student achievement." Suggestions that the author can convey, to colleagues: (a) In delivering learning materials do not use the lecture method; (b) Choose the right learning methods and strategies; (c) Experience in this research activity should motivate fellow teachers to conduct research.